Functional features and possibilities for the implementation of tactile Internet - Simeonova, Tsvetelina; Kadrev, Vasil (Yearbook Telecommunications, 2022)
According to the ITU, tactile Internet is a network that combines ultra-low latency with extremely high availability, reliability and security. Tactile Internet provides real-time monitoring, management and control of remote infrastructure and devices that support haptic communications. The purpose of this work is to identify the functional features and capabilities for the implementation of tactile Internet. The results are related to the summary of typical use cases, based on the key parameters latency and reliability. A key point is the comparative analysis of the use cases in terms of key parameters and sectors of influence.